Ethnic Studies Council of CSUCI Bylaws
The Ethnic Studies Council (ESC) was founded by Ethnic Studies faculty and other faculty who shared concerns and advocacy for the development and growth of ES on our campus. With the passage of AB1460, the Senate created an ad-hoc Ethnic Studies Task Force to make sure our campus was in compliance with the law. Members of the ESC served on this committee. The ESC became critical to our campus as we became the body that has continued to do the work to create and submit new curriculum/courses and remain active in the CSU-wide efforts to build ES. We are the body that is navigating budgetary and other relevant issues for our campus. Yet, the ESC is not a formally recognized body on this campus. The ESC worked Fall 2022 to research other CSU campuses and attempt to figure out what an ESC could look like as the leadership for our own campus.